Hazai termékek a turizmusban: helyi élelmiszerek és hungarikumok turisztikai attrakciós potenciálja - Patyiné Stiblo, Mária (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
My aim is to reveal the role of regional food products in terms of the local cunsumers’ touristic motivation system. In order to do this, in the form of a quantitative survey I examine the respondents’consumption patterns, sources of information and knowledge and my purpose is to uncover some elements of the consumption motivation and system of attitudes. In the planned research, I investigate mainly the local consumers’ level of knowledge and attitudes with regional products and hungaricums. I choose the scope of components and touristic products from those which are under the origin protection of the European Union and from those which are products of the HÍR-collection or which are among the services of rural guest-table run by small-scale producers.